Precambrian Geology of China - Zhai, Mingguo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book is the first contribution to the overview of Precambrian geology of China. It covers Precambrian geology of the North China Craton, the South China Craton, and the Tarim Craton, as well as other smaller blocks in the Chinese orogenic belts. It provides systematic concepts of the Chinese paleo-continents and incorporates the most up-to-date achievements. Edited by many of the active researchers working at the forefront of the related fields, it contributes greatly to the international Precambrian geology community, and would be of interest to geoscientists working in the research field of geology of China and Precambrian geodynamics.
Keywords: Geology; Geochemistry; Geology; Geochemistry